PENGARUH MODEL PEMBELAJARAN COOPERATIVE SCRIPT BERBANTUAN MEDIA STRIP STORY TERHADAP KOMPETENSI PENGETAHUAN BAHASA INDONESIA - luh putu agustina wulandari (Universitas Pendidikan Ganesha, 2018)
This study aims to determine the significant effect of the knowledge competency of Bahasa Indonesia between the group of students who were studied through cooperative script learning model with strip story media with the group of students who were not studied through cooperative script learning model with strip story media on the fourth grade of students gugus IV Kuta Selatan academic year 2017/2018. This type of study is a quasi experiment with nonquivalent control group research design. The population of study is the fourth grade of students Gugus IV Kuta Selatan academic year 2017/2018 in total 416 students. The sample is determined by random sampling technique. The sample of study is the students of class IVA SD No. 10 Jimbaran as experimental group and the students of class IVA SD No. 4 Jimbaran as control group. The mastery data of the knowledge competency of Bahasa Indonesia is collected by the instrument in form of 23 questions of multiple-choice objective test which is validated. The mastery data of the knowledge competency of Bahasa Indonesia is analyzed by t-test. The result of the analysis shows that there is a significant influence on the mastery of the knowledge competency of Bahasa Indonesia between the group of students who were studied through cooperative script learning model with strip story media with the group of students who were not studied through cooperative script learning model with strip story media on the fourth grade of students gugus IV Kuta Selatan academic year 2017/2018. It is proved by thitung = and at the significant level 5% ( =0,05) with dk = (35+30) – 2 = 63 obtained ttabel = 2,000. Based on test criteria thitung = > ttabel (α=0,05) = 2,000. As well as average score of the mastery of knowledge competency of Bahasa Indonesia of experimental students X1= 0,46 > X2= 0,20 the average score of the mastery of knowledge competency of Bahasa Indonesia of control group students. Thus it can be concluded that cooperative script learning with story strip media influence on the mastery of the knowledge competency of Bahasa Indonesia on the fourth grade of students in SD Gugus IV Kuta Selatan academic year 2017/2018.